THE PRECISION OF VOCABULARY IN PRESCHOOL CHILDREN - Torres - Montero, Aymet Daniuska (2019)
The present work is directed to solve the insufficiencies that appear in the vocabulary development in the children of the preschool level. To solve this problem, children's riddles will be developed that allow the assimilation of the meaning of the words and with it the precision of their vocabulary. The proposed children's riddles are established in three contents: Animals, plants, fruits and vegetables. In this investigation the population is constituted by twenty-seven children of the sixth year of life of the school: Orestes Gutierrez; a random sample of 14 children is taken, which represents the random selection criterion, which constitutes fifty-two percent of the population. On the other hand, it can be said that riddles are popular sayings, children's games of ingenuity that aim to entertain and entertain children while contributing to their learning, and teaching a new vocabulary. For what the author considers that the topic is very topical and scientific importance because from the proposal develops the ability to observe and with it the children learn to focus on the most important details, to compare and imagine what makes possible In a playful way, children understand and extend the meaning of the words. In addition to being innovative in terms of the sample of an unusual proposal and little used in educators, to direct the educational process as such riddles are.